Stop Bullying Education As A Prevention Effort Using Video To Know The Knowledge Of Children At Elementary School - Intan Fazrin; Rizma El Walid (Journal for Quality in Public Health, 2024)
Bullying is behavior that is intended to injure either directly or indirectly carried out by a strong party against a weak party. This research aims to identify children's knowledge pre and post education is carried out to stop bullying using video at elementary scchool Kalipang 02. This research design uses Pre Experiment Designs with Simple Random Sampling technique. A sample of 25 respondents was obtained. Statistical test results using Wilcoxon test. The results of the research show that before education, the majority of children had a level of knowledge of less than 6 children with a percentage (25%) after education became 0 children with a percentage of (0%), then before education children with a sufficient level of knowledge were 16 children with a percentage (66.7 %) after education, the level of knowledge became 1 child with a percentage of (4.1%) and after education, the majority of children had a good level of knowledge, which increased to 23 children with a percentage of (95.9%). These results indicate that video has the potential to be an effective tool in providing better knowledge about bullying to the child. The results of data analysis show that the p value of 0.000 is smaller than 0.05, so it can be concluded that the "hypothesis is accepted" which means the delivery of the material bullying using video media has an effect on the knowledge of class V children at elementary school Kalipang 02. Conclusion: Based on the research results, it was concluded that education to stop bullying through video has a positive impact in increasing children's knowledge about bullying at elementary school Kalipang 02. This approach provides evidence that video can be used as an effective means of prevention in overcoming bullying among children.